2018
DOI: 10.1371/journal.pone.0203067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perinatal blood pressure on maternal brain functional connectivity

Abstract: Perinatal hypertensive disorder including pre-eclampsia is a systemic syndrome that occurs in 3–5% of pregnant women. It can result in various degrees of brain damage. A recent study suggested that even gestational hypertension without proteinuria can cause cardiovascular or cognitive impairments later in life. We hypothesized that perinatal hypertension affects the brain functional connectivity (FC) regardless of the clinical manifestation of brain functional impairment. In the present study, we analyzed regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…In our sample, fathers were significantly more aware and less distressed about typical trial characteristics. We hypothesize that mothers are more emotionally distressed at the moment of consent and often still bear the consequences from medical conditions leading to preterm birth that also affect cognitive functioning and possibly memory [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, fathers were significantly more aware and less distressed about typical trial characteristics. We hypothesize that mothers are more emotionally distressed at the moment of consent and often still bear the consequences from medical conditions leading to preterm birth that also affect cognitive functioning and possibly memory [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…this study suggest that functional network alterations in formerly pre-eclamptic women are comparable with those seen in hypertensive patients. Additionally, it has been shown that the connectivity in the bilateral orbitofrontal gyri, measured within 10 days after delivery, correlated negatively with the diastolic blood pressure in both cases with PE and controls 36 . This suggests that increased diastolic blood pressure, as present in hypertension, with or without PE, may affect the functional brain network.…”
Section: Discussionmentioning
confidence: 99%
“… Uric acid and lactate dehydrogenase levels are one of the indicators reflecting the severity of endothelial dysfunction, which have a high correlation with RPLS. This study found that both significantly increased in the RPLS group, suggesting that endothelial inflammatory injury might play an important role in the process of brain edema of RPLS, which could be used as a predictor of the degree of brain edema of RPLS [ 22 24 ]. This study found that the ALT level in the RPLS group was higher than that in the non-RPLS group, and the AST and ALT levels in the two groups were significantly higher than the normal value, indicating varying degrees of damage to the liver function of pregnant women with pregnancy-induced hypertension or SPE/E combined with RPLS, but this was not a specific index [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid and lactate dehydrogenase levels are one of the indicators reflecting the severity of endothelial dysfunction, which have a high correlation with RPLS. This study found that both significantly increased in the RPLS group, suggesting that endothelial inflammatory injury might play an important role in the process of brain edema of RPLS, which could be used as a predictor of the degree of brain edema of RPLS [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%